INFLUENCE OF PRODUCT INNOVATION, PRODUCT QUALITY, PRICE AND PROMOTION ON BRAND AWARENESS PT. WULING KUMALA TOMOHON - Sartika Marselina Siwi; Silvya L. Mandey; Imelda WJ Ogi (Research Parks Publishers, 2023)
Currently newcomer car products are not only colored with brands from Japan, Korea, Germany or America. Now the Chinese state is releasing car products that cannot be underestimated by its competitors. The Wuling brand car, which was present in Indonesia for the first time in 2015, only took 3 years to become one of the 10 best-selling car brands in Indonesia according to GAKAINDO data. In 2017 Wuling dealers were present in Manado city and in 2018 Wuling dealers opened a branch in Tomohon city for market penetration in North Sulawesi Province. As a newcomer car, Brand Awareness must be able to appear in every product owned by a Wuling brand car. So that people can easily recognize and identify each product that is produced by the Wuling brand. This study discusses the effect of product innovation, product quality, price and promotion on Brand Awareness of PT. Wuling Kumala Tomohon, where there are still consumers who cannot distinguish Wuling car brands from other car brands and know about Wuling car brands. The purpose of this research is to see how product innovation, product quality, price and promotion affect Brand Awareness. The analytical method used was validity, reliability, classical assumptions and multiple regression using the SPSS Version 25 application. The results showed that partially each variable of product innovation, product quality, price and promotion had a positive and significant effect on the Wuling brand PT. Kumala Tomohon. Likewise simultaneously product innovation, product quality, prices and promotions have a positive and significant effect on the Brand Awareness of PT. Wuling Kumala Tomohon